A 3.9 ppm/○C, 31.5 ppm/V ultra-low-power subthreshold CMOS-only voltage reference. (February 2020) - Liao, Jinrui; Zeng, Yanhan; Li, Jintao; Yang, Jingci; Tan, Hong-Zhou
Abstract: This paper presents an ultra-low-power CMOS voltage reference based on the 0.18 μ m standard CMOS technology. A temperature coefficient (TC) of 3.9 ppm/ ○ C without resistors or special devices is obtained by utilizing both the MOS transistor working in the deep triode region and the body bias technique. The current consumption in the minimum supply voltage of 0.85 V is as low as 96 nA. The line sensibility (LS) is 31.5 ppm/V when the supply voltage varies form 0.85 V to 3 V while the power supply rejection ration (PSRR) are −86.6 dB at 1 Hz and −50.2 dB at 100 Hz.